Enhancing student agency through platform agnosticism and heuristic teaching - Chris Friend (Discover Education)
Abstract Technology-infused classrooms sometimes feel like tech-support sessions, where students struggle to learn platform interfaces during their process of content creation. Especially in courses where technology is the medium, not the subject matter, time and attention directed toward troubleshooting can feel like distractions from the “real” work of the class. The response to classroom tech trouble—as well as a common approach to technology textbooks and manuals—involves step-by-step, click-by-click instructions and screenshots of each interface element in sequence. This article objects to that approach on account of the responsive design of modern platforms and the dynamic nature of modern interfaces. By using an intentionally less-helpful approach to classroom tech, instructors can (1) avoid tech-support responsibilities; (2) show that tech-tool use is intentional, rather than inevitable; and (3) promote student agency through experiential learning. The article concludes with the assertion that teachers should pay less attention to the specific technological tools they use/suggest and pay more attention to the generic functions of those technologies. Overall, I argue that teachers should take a heuristic approach to ed-tech and provide instruction that is platform-agnostic and allow students to select what they see as the best tool to complete a given task.